Structure, membrane topology and influence of cholesterol of the membrane proximal region: transmembrane helical anchor sequence of gp41 from HIV - Aisenbrey, Christopher (Sci Rep, 2020)
During the first steps of HIV infection the Env subunit gp41 is thought to establish contact between the membranes and to be the main driver of fusion. Here we investigated in liquid crystalline membranes the structure and cholesterol recognition of constructs made of a gp41 external region carrying a cholesterol recognition amino acid consensus (CRAC) motif and a hydrophobic membrane anchoring sequence. CD- und ATR-FTIR spectroscopies indicate that the constructs adopt a high degree of helical secondary structure in membrane environments. Furthermore, (15)N and (2)H solid-state NMR spectra of gp41 polypeptides reconstituted into uniaxially oriented bilayers agree with the CRAC domain being an extension of the transmembrane helix. Upon addition of cholesterol the CRAC NMR spectra remain largely unaffected when being associated with the native gp41 transmembrane sequence but its topology changes when anchored in the membrane by a hydrophobic model sequence. The (2)H solid-state NMR spectra of deuterated cholesterol are indicative of a stronger influence of the model sequence on this lipid when compared to the native gp41 sequence. These observations are suggestive of a strong coupling between the transmembrane and the membrane proximal region of gp41 possibly enforced by oligomerization of the transmembrane helical region.